Peran Nilai-Nilai Sumpah Pemuda Dalam Membentuk Karakter Peserta Didik Di SMAN 18 Jakarta - Herdin Muhtarom; Gery Erlangga (Criksetra: Jurnal Pendidikan Sejarah, 2021)
Starting from a problem in the school environment related to the event held by the school regarding the youth oath event which was limited to celebrating it without interpreting the values of the youth oath in the activity. So that in this study, it has the aim of being able to determine the level of understanding of SMAN 18 Jakarta students in understanding the contents of the youth oath incident as a role in shaping character. This study uses the Mixed Methods method with the Sequential Explanatory model type. Then the data collection technique was by distributing questionnaires to students of SMAN 18 Jakarta as the research sample. The results show that the understanding of the role of youth oath values in shaping the character of students of SMAN 18 Jakarta understands the meaning of the content in the youth oath incident with a data percentage of 67.7% expressing understanding of the values contained in the youth oath. As a millennial generation, it should be able to implement an understanding of the values of the youth oath so as to increase the sense of nationalism in the millennial generation.